Cost-effectiveness of exercise therapy in the treatment of non-specific neck pain and low back pain: a systematic review with meta-analysis. Issue 3 (20th April 2018) - Miyamoto, Gisela Cristiane; Lin, Chung-Wei Christine; Cabral, Cristina Maria Nunes; van Dongen, Johanna M; van Tulder, Maurits W
Abstract : Objective: To investigate the cost-effectiveness of exercise therapy in the treatment of patients with non-specific neck pain and low back pain. Design: Systematic review of economic evaluations. Data sources: The search was performed in 5 clinical and 3 economic electronic databases. Eligibility criteria for selecting studies: We included economic evaluations performed alongside randomised controlled trials. Differences in costs and effects were pooled in a meta-analysis, if possible, and incremental cost-utility ratios (ICUR) were descriptively analysed. Results: Twenty-two studies were included. On average, exercise therapy was associated with lower costs and larger effects for quality-adjusted life-year (QALY) in comparison with usual care for subacute and chronic low back pain from a healthcare perspective (based on ICUR). Exercise therapy had similar costs and effect for QALY in comparison with other interventions for neck pain from a societal perspective, and subacute and chronic low back pain from a healthcare perspective. There was limited or inconsistent evidence on the cost-effectiveness of exercise therapy compared with usual care for neck pain and acute low back pain, other interventions for acute low back pain and different types of exercise therapy for neck pain and low back pain. Conclusions: Exercise therapy seems to be cost-effective compared with usual care for subacute and chronic low back pain. Exercise therapy was not (more) cost-effective compared with other interventions for neck pain and low back pain. The cost-utility estimates are rather uncertain, indicating that more economic evaluations are needed. Registration: PROSPERO, CRD42017059025.